2020
DOI: 10.1080/23299460.2020.1785678
|View full text |Cite
|
Sign up to set email alerts
|

Embedding responsible innovation within synthetic biology research and innovation: insights from a UK multi-disciplinary research centre

Abstract: Over the last decade the discourse of responsible innovation (RI) has become a significant feature of debates concerning the relationships between science, innovation and society in the fields of biosciences and biotechnologies. We document how this discourse has evolved over the period 2014-2019 at a Synthetic Biology Research Centre hosted within a University in the UK (BrisSynBio). We describe how an approach to RI has evolved to include but go beyond public engagement, by encouraging practices aimed at ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…In their recent review, Schuijff and Dijkstra (2020) note that where such approaches are observed, these tend to be aligned with just one of the RI dimensions described by Stilgoe et al (2013) rather than all four in an integrated manner. That said, we also note instances of experimentation around RI as an integrated approach, for example within some of the Synthetic Biology Research Centres and some Centres for Doctoral Training (Pansera et al, 2020;Reinsborough, 2020).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In their recent review, Schuijff and Dijkstra (2020) note that where such approaches are observed, these tend to be aligned with just one of the RI dimensions described by Stilgoe et al (2013) rather than all four in an integrated manner. That said, we also note instances of experimentation around RI as an integrated approach, for example within some of the Synthetic Biology Research Centres and some Centres for Doctoral Training (Pansera et al, 2020;Reinsborough, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Our analysis points to a range of responses in turn at individual and organisational levels. In a small number of cases RI appears to have been embraced in a substantive way (Pansera et al, 2020). At the other end of the spectrum there is evidence of outright resistance (Kuntz, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Institutional and organizational level empirical investigations and assessments include reducing inequality through 3D printing in US public libraries (Woodson, Telendii, and Tolliver 2020), embedding responsible innovation in a UK synthetic biology multi-disciplinary research center (Pansera et al 2020), researcher expectations and practices around open science in Australia (Lacey, Coates, and Herington 2020), the integration of policy-driven grand challenges into research agendas in German university settings (Kaltenbrunner 2020), and the problematic paradigm of 'social license to operate' as used within synthetic biology public engagement discourses (Delborne, Kokotovich, and Lunshof 2020).…”
Section: Closing Out Twenty-twenty On a Positive Notementioning
confidence: 99%
“…The theme of art-science collaborations as the basis for "deliberative discussions on research agendas and direction" is taken up by Michael Reinsborough [2] in this issue. A broader analysis of the responsible innovation and public engagement programme at BrisSynBio can be found in Pansera et al [3].…”
Section: Introduction (By Darian Meacham)mentioning
confidence: 99%
“…reflections on methodological approaches to 'making'. 3 Maria Fannin's contribution to this dossier is a reflection on the collaboration and the questions and challenges it presented as emblematic of cross-disciplinary collaboration in synthetic biology, specifically those collaborations involving social scientists, researchers from the humanities and artists. Connor's piece offers an account of and reflection on the Blood Culture Project.…”
Section: Introduction (By Darian Meacham)mentioning
confidence: 99%